Penurunan Kadar Asam Sianida (HCN) pada Umbi Gadung (Dioscorea Hispida Dennst) Melalui Proses Ekstraksi dengan Kombinasi Konsentrasi NaHCO₃ dan NaCl. - Nazua, Hanani; Ainurrohmah, Syafika; Saputro, Erwan Adi; Triana, Nurul Widji (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
The utilization of gadung tubers as an alternative food has limitations due to the presence of cyanide content, which can cause poisoning. The cyanide content is cyanogenic glycosides, which can be enzymatically hydrolyzed to form cyanide acid compounds (HCN). The cyanide content in gadung tubers averages around 362 ppm, while the safe limit for consumption of cyanide acid levels is ≤ 10 ppm. This study aims to reduce the cyanide acid content in gadung tubers through a maceration extraction process with a combination of Sodium Bicarbonate (NaHCO₃) and Sodium Chloride (NaCl) solvents so that it complies with the World Health Organization (WHO) standards. Gadung tuber extract was obtained from maceration extraction for 30 minutes in each solvent. Testing methods for cyanide acid in Gadung tubers include Titrimetry, Spectrophotometry, and Organoleptic. The combination of high concentrations of Sodium Bicarbonate (NaHCO₃) and Sodium Chloride (NaCl) can help reduce cyanide acid levels in gadung tubers. The initial cyanide acid level of 47.02 mg/kg can be reduced with the best concentration combination (10:15)%, where the analysis results in titrimetry amounted to 9 mg/kg, while in spectrophotometry it was 9.5 mg/kg. This shows that cyanide acid levels can be reduced by 80-81% so that these levels meet World Health Organization (WHO) standards.